A Kinetic Study on Sesame Cake Protein Hydrolysis by Alcalase - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (WILEY, 2011)
In the present study, the hydrolysis of sesame cake protein was performed by Alcalase, a bacterial protease produced by Bacillus licheniformis, to investigate the reaction kinetics of sesame cake hydrolysis and to determine decay and product inhibition effects for Alcalase. The reactions were carried out for 10 min in 0.1 L of aqueous solutions containing 10, 15, 20, 25, and 30 g protein/L at various temperature and pH values. To determine decay and product inhibition effects for Alcalase, a series of inhibition experiments were conducted with the addition of various amounts of hydrolysate. The reaction kinetics was investigated by initial rate approach. The initial reaction rates were determined from the slopes of the linear models that fitted to the experimental data. The kinetic parameters, K-m and V-max, were estimated as 41.17 g/L and 9.24 meqv/L. min. The Lineweaver-Burk plots showed that the type of inhibition for Alcalase determined as uncompetitive, and the inhibition constant, K-i, was estimated as 38.24% (hydrolysate/substrate mixture).
Keywords: Alcalase; hydrolysis kinetics; Lineweaver-Burk; product inhibition; sesame cake protein; ENZYMATIC-HYDROLYSIS; SOLUBILITY; INDICUM; PH; Food Science & Technology